Technical Assessment on the Current Technique of Solid Waste Disposal at Bercham, Ipoh - Nasibah bt Isbullah, Nasibah (Universiti Teknologi Petronas, 2009)
Solid waste disposal has become a pressing problem due to a number of factors; growth in population as well as change in lifestyle with the consumption of more modern materials and disposal products. Problems and challenges related to dumping site need to be studied and analyzed. It helps for better understanding in managing municipal solid waste. This project involves research work on landfill site condition, environmental impact on current practice, technique of solid waste disposal as well as closure and post closure of landfill. Site investigation was conducted at Bercham dumpsite, Ipoh to observe the condition and activities at the site. There are challenges encountered which are uncontrolled scavengers activities, nuisance from rodens and vermins and other technical challenges. Since the expenses for the management of municipal waste are relatively high in Malaysia and almost no value is being generated from the waste material. Therefore, in this study, methane gas production was estimated can give benefit in the future in term of generating energy. From a sample of waste at Bercham dumpsite, the chemical formula for waste at Bercham dumpsite obtained is C11H23O8N. The result shows that 451.09 m3 of gas generated from a tonne of waste. This volume is considered average for sanitary landfill. From the results, it shows that the site has the potential to utilize the energy generated